Antihyperglycemic, antioxidant activities of tucumã oil (Astrocaryum vulgare) in alloxan-induced diabetic mice, and identification of fatty acid profile by gas chromatograph: New natural source to treat hyperglycemia - Baldissera M.D. (2017)
© 2017 Elsevier B.V.The aim of the study was to investigate the effect of the oral administration of tucumã oil (Astrocaryum vulgare) on glucose and insulin levels, oxidative status, and pancreatic genotoxic parameters of alloxan-induced diabetic mice. The animals were divided into four groups (n = 6 each): control/water; control/tucumã oil; diabetic/water; diabetic/tucumã oil treated for 14 days with 5.0 mL kg−1 via oral gavage. Gas chromatograph characterization demonstrated that oleic/elaidic fatty acid is the most abundant component present in this oil, followed by palmitic and stearic fatty acids. Our results demonstrated an increase (p < 0.05) in water and food intake, blood glucose, thiobarbituric acid reactive species (TBARS) levels, damage index, and frequency of damage; conversely body weight, insulin levels, catalase (CAT) and superoxide dismutase (SOD) activities, and cell viability were decreased in the diabetic/water group compared to the control/water group. The treatment with tucumã oil prevented these alterations in the diabetic/tucumã oil group compared to the diabetic/water group, and restored these parameters near to the control/water group. In summary, our findings demonstrated that treatment with tucumã oil causes a hypoglycemic effect improving insulin levels and antioxidant/oxidant status, and has a protector effect against pancreatic damage induced by oxidative stress in alloxan-induced diabetic mice.